Photoresponse properties of CdSe thin film photodetector - Shelke, Nitin T.; Karle, S. C.; Karche, B. R. (Journal of Materials Science-Materials in Electronics, 2020)
In the present investigation, the performance of highly sensitive photodetector based on CdSe thin film has been demonstrated. The cadmium selenide (CdSe) films were deposited successfully by spray pyrolysis method on glass substrate. The as-deposited films were used as visible light detector. Further, the structural, morphological, and optical properties of CdSe films were investigated through X-ray diffraction (XRD), scanning electron microscopy (SEM), atomic force microscopy, and optical absorption spectrophotometer. The XRD studies show that the produced samples are polycrystalline in nature. A UV-Visible absorbance spectrum indicates direct allowed transition with bandgap about 1.75 eV. The SEM micrographs depict uniformly distributed well defined uneven hexagonal grains. The CdSe film-based photodetector exhibits high responsivity, detectivity and shows an ultrafast photoresponse. The excellent photoresponse and high photosensitivity of CdSe film makes it a strong candidate for high-performance photodetectors.